2018
DOI: 10.3389/fpsyg.2018.02492
|View full text |Cite
|
Sign up to set email alerts
|

Soundscape Assessment of Aircraft Height and Size

Abstract: It is accepted knowledge that, for a given equivalent sound pressure level, sounds produced by planes are worse received from local communities than other sources related to transportation. Very little is known on the reasons for this special status, including any interactions that non-acoustical factors may have in listener assessments. Here we focus on one of such factors, the multisensory aspect of aircraft events. We propose a method to assess the visual impact of perceived aircraft height and size, beyond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Further analysis of the data showed that almost 16% of the participants did not perceive the sound had an elevation: they placed it at the correct azimuth , but with . This difficulty in the vertical axis (elevation) was also observed in experiments correlating the perceived height of planes with their perceived noise 40 . In those experiments, observers tended to make a wrong assessment of the altitude of passing aircraft and thus alter their acoustic judgment.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Further analysis of the data showed that almost 16% of the participants did not perceive the sound had an elevation: they placed it at the correct azimuth , but with . This difficulty in the vertical axis (elevation) was also observed in experiments correlating the perceived height of planes with their perceived noise 40 . In those experiments, observers tended to make a wrong assessment of the altitude of passing aircraft and thus alter their acoustic judgment.…”
Section: Discussionsupporting
confidence: 52%
“…In those experiments, observers tended to make a wrong assessment of the altitude of passing aircraft and thus alter their acoustic judgment. Further studies on this uncertainty in position sources in elevation may help to explain the large variability of annoyance statements due to aircraft noise in comparison to what is reported with other transportation sources for the same acoustic level 40 , 41 .…”
Section: Discussionmentioning
confidence: 91%
“…Table 1 also highlights how the sound sources positioned along azimuth angles are easier to localize than sources at different elevations. This is crucial for 3D soundscape designers (Hruby, 2019 ) and for interpreting data in a cityscape (Memoli et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is very challenging to estimate the distance of a source, such as the altitude of an overflying plane, and this results in large errors in real life (Memoli et al, 2018 ). Localization improves when a user is allowed to move towards the source, which is crucial for audio-only AR environments (e.g., a voice describing places).…”
Section: Spatial Sound: From Delivery To Perceptionmentioning
confidence: 99%
See 1 more Smart Citation